Promoters of the dhs-21 gene encoding dicarbonyl/l-xylulose reductase in Caenorhabditis elegans - Sơn, Lê Thọ; Ahnn, Joohong; Cho, Jeong Hoon; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2018)
Dicarbonyl/L-xylulose (DCXR) was identified as a dehydrogenase. This type of enzyme was presented in various forms of lives including bacteria, fungi, plants and animals. Generally, it converts L-xylulose to xylitol in the presence of either cofactor NADH or NADPH in vitro. Previous studies reported the biochemistry properties and crystal structure but largely uncovered biological roles of DCXRs. It was impossible to dissect the functions in mice or human cells that had many DCXR homologs in their genomes. Interestingly, the wild-type Caenorhabditis elegans, a well-known model organism in biological research, has only nuclear genomic dhs-21 that encodes a unique homologous DCXR. Thus Ce.dhs-21 and the host C. elegans were relevant for investigation of the physiologically-vital functions of the DCXR. This research aimed to the expression of dhs-21 in vivo. We defined three promoters , manipulated three relative reporter-constructs that conjugated the dhs-21 gene and Green Flouresent Protein (known as GFP) one. The construct vectors were transferred into wild-type C. elegans N2 and as well as the hermaphroditic loss of function dhs-21(jh129) by microinjection. In the results, we found that the expression pattern of dhs-21 under the only p2-promoter construct was stable and similar to immunogold Electric Microscopy (EM) images. The dhs-21 gene was expressed in both sexes of at all larval stages till the deaths of worms. DHS-21 was expressed in the cytosol of the intestinal, gonad sheath and uterous seam cell (utse).